Volunteers with and without a history of head and neck cancer swallowing, saliva, and QOL in head/neck cancer - Rodrigues, Alana Semenzin [UNESP]; Libera, Juliana Dela [UNESP]; Januzzi, Marcella Santos [UNESP]; de Caxias, Fernanda Pereira [UNESP]; Túrcio, Karina Helga Leal [UNESP]; Moreira, Samantha [UNESP]; Goiato, Marcelo Coelho [UNESP]; Santos, Daniela Micheline dos [UNESP] (Springer Nature, 2025)
This observational cross-sectional study aimed to evaluate swallowing in volunteers with and without a history of head and neck cancer using electromyographic amplitude, salivary flow, and quality of life. We analyzed 30 volunteers, 15 with a history of cancer (test group), and 15 without (control group), all wearing bimaxillary complete dentures for at least 6 months. Electromyographic amplitude of the masseter, temporal, and suprahyoid muscles was assessed during mandibular rest and during swallowing of nectar, liquid, pudding, and solid foods, using a surface electromyograph. Salivary flow was measured by collecting unstimulated saliva from volunteers while wearing their dentures. Dysphagia and its impact on quality of life were assessed using the MD Anderson Dysphagia Inventory (MDADI). Data were analyzed using normality tests (Shapiro–Wilk) and appropriate statistical tests (T Student or Mann–Whitney). No statistically significant differences were found between the test and control groups in electromyographic amplitude of the temporal, masseter, and suprahyoid muscles during rest (p = 0.468/0.663/0.619) and swallowing (p = 0.240/0.830/0.870 for nectar, p = 0.101/0.760/0.838 for liquid, p = 0.056/0.902/0.967 for pudding, p = 0.494/0.805/0.116 for solid). There was also no significant difference in salivary flow (p = 0.438). However, significant differences were found in MDADI scores (p < 0.001), especially in the emotional domain (p < 0.001), indicating a major impact of dysphagia on quality of life in these patients.